Insights into “Yin Rhyme”: Analysis of nonvolatile components in Tieguanyin oolong tea during the manufacturing process - Qiuming Li; Qingcai Hu; Xiaoxi Ou; Jihang He; Xinru Yu; Yunzhi Hao; Yucheng Zheng; Yun Sun (Food Chemistry: X, 2024)
Tieguanyin (TGY) is renowned for its distinctive “Yin Rhyme” flavor. To elucidate the underlying formation mechanism, we conducted sensory evaluations, electronic tongue analysis, and widely-targeted metabolomics. Our sensory evaluations and electronic tongue results indicated that TGY exhibits a thick and mellow taste profile, contributing to the “Yin Rhyme” flavor. Metabolomics analysis of tea products revealed that TGY shows significantly higher concentrations of umami substances (L-glutamate, L-theanine) and bitter substances (valine, catechins) compared to Jinguanyin (JGY). Additionally, metabolomic analysis during different oolong tea processing stages revealed significant differences in 21 substances, including L-glutamate, L-theanine, valine, and catechins, between fresh leaves of both varieties. These substances exhibited distinct fluctuation patterns during processing, indicating that the cultivar plays a crucial role in developing the “Yin Rhyme” flavor, which was enhanced throughout processing. This study provides a theoretical foundation for understanding the formation of the unique “Yin Rhyme” flavor of TGY.